The glocalization of death in the digital age: traits and limits - Toplean, Adela (Frontiers in Communication, 2024)
This perspective article explores the interplay between death and glocalization in digitally saturated societies. The central question driving our perspective is how societal responses to death reflect and inform the process of glocalization within the context of increasing digital connectivity. The paper argues that societal response to death provides a unique lens on how global digital trends intersect with deep-seated beliefs and traditions in glocalization dynamics. Thus, the main section of the article (Section 3) examines the traits and limitations of digital glocalization in mortality contexts, revealing its multifaceted nature: digital glocalization is relational, post-metaphysical, naturally occurring, and a boundary solution to the crisis. Constraints in glocal forging in the context of death include interpersonal challenges, social alienation, evolving localisms, religious considerations, and timing. Our perspective from brief ethnographic insights in contemporary Romania underscores the fusion of ancient customs, digital tools, and religious beliefs in shaping distinctive responses to death in digitally enriched environments. Ultimately, the research concludes that death serves as a catalyst for glocalization, harmonizing local traditions and digital advancements in navigating the complexities of life and loss in the digital age, portraying death as the great "glocalizer."